ELT STUDENTS’ PERSPECTIVES ON THE IMPACT OF ONLINE ROLE – PLAYING GAMES IN ENGLISH LANGUAGE ACQUISITION - Rama Pringgadani (Jurnal Ilmiah Spectral, 2026)
Online RPGs are games that establish a highly detailed world where players can immerse themselves to become any character they have dreamed of. For the past three years, Online RPGs have been used creatively by students as a learning medium beyond conventional classroom learning because this approach makes the learning process much more bearable and enjoyable, and doesn’t make students bored easily. The purpose of this study is to examine ELT students’ perspectives on online RPGs in English language acquisition. The study was conducted at Universitas Tanjungpura, specifically in the English Education Department. The study employs a qualitative survey that combines open–ended and closed–ended questions to gather detailed responses from respondents.   The participants consisted of 15 sixth-semester students who were active online RPG players. The findings showed that online RPGs offer many benefits for language acquisition. One of the profound aspects was their enhanced reading comprehension. However, an internal issue, such as a student’s confidence, and an external issue, such as a toxic player, could interfere with their language acquisition. In conclusion, ELT students have a positive attitude toward online RPGs in English language acquisition.